AN ANALYSIS OF GIVING REINFORCEMENT BY TEACHER IN STUDENTS’ LEARNING ENGLISH MOTIVATION OF SMP MUHAMMADIYAH IWAY JEPARA ACADEMIC YEAR 2012/2013 - Dewi, Hesti Tusiana (Premise: Journal of English Education and Applied Linguistics, 2013)
This undergraduate thesis analyzes about giving reinforcement by teacher to motivate students in learning English. Language learning is not a set of easy steps that can be programmed in a quick do-it-yourself kit. People achieve fluency in a foreign language solely within the activity in the classroom. Process in the classroom become the important part to transfer knowledge so the result of the learning process will be maximal. Reinforcement is one of the important steps in learning, can be functioned to motivate students in learning process.There are three problems of this study, (1) Does teacher give reinforcement to motivate the students in learning English ? (2) What is the effect of reinforcement toward the students’ motivation in learning English? (3) What factors cause the unmotivated students in learning English? This research is designed as a qualitative research and conducted in odd semester at the Eight B grade of SMP Muhammadiyah I Way Jepara East Lampung Academic Year 2012/2013. As a source of data, the writer utilized two instruments  to get the data by using observation and questionnaires. The analysis of the data used comparative method enclose reduction the data, categorization and synthesizing the data.The result of this analysis are (1) the teacher have given reinforcement in learning English, it can be proven by seeing percentage of the analysis result that 75 % teacher often use reinforcement in learning English and 25 % teacher rare use some activities that indicated the teacher have given reinforcement in learning English.(2) the students are motivated after getting reinforcement in Learning English. (3) some activities that cause students are unmotivated in Learning English.By studying and analyzing giving reinforcement in learning English, the writer expects an English teacher should give reinforcement in all learning process especially learning English and should avoid some factors that cause the students are unmotivated in learning English because by giving reinforcement in learning the students are motivated in learning English. It means that giving reinforcement by teacher can motivate students in learning English.